Impact of virtual education on students in the face-to-face modality of the public administration career due to the covid-19 pandemic - Torres Vargas, Washington Paúl; Jimbo Santana, Patricia Rosalía; Agurto Gómez, Daniel Alejandro; Rivadeneira Enríquez, María Micaela; Aponte Gutiérrez, Thalía Lizbeth (SATHIRI, 2022)
The present investigation is a mixed quantitative and qualitative type, where the students of the face-to-face modality of the Faculty of Administrative Sciences, Public Administration career have been considered as a sample. This study aims to decipher the digital divide and the knowledge about information and communication technologies that students have to face virtuality. In addition, it is intended to identify the time they use to develop their studies, and carry out their personal activities. In this sense, digital connectivity and time management have been considered as study variables. Among the most visible results are the precarious connectivity, which minimizes the quality of learning for the student, the opportunity presented for teachers to use new tools, the prolonged use of devices and the Internet, the procrastination of academic activities and weakening of the socio-emotional health of the students.
Keywords: Pandemy; Covid-19; information and communication technologies; higher education; virtual education